2019
DOI: 10.1007/s10098-019-01734-9
|View full text |Cite
|
Sign up to set email alerts
|

Not in my hiking trail? Acceptance of wind farms in the Austrian Alps

Abstract: Large-scale wind power projects are one of the bearers of hope for a transition toward low-carbon electricity systems. The question of social acceptance of such projects near residential areas, or acceptance of the technology in general, has received significant attention in the scientific literature. Less attention has been placed on acceptability of wind farms in sparsely inhabited mountain areas; the focus of this paper therefore is on acceptance of wind farms in the Austrian Alps from the perspective of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 51 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Liu and Stevens [ 65 ] support the siting of wind energy infrastructure in mountainous regions and preferably above hilltops due to performance reasons. Several studies show that the development of renewable energy facilities in high-elevation mountainous regions often lacks of social acceptance [ 53 , 54 , 66 ]. This present study confirms prior findings.…”
Section: Discussionmentioning
confidence: 99%
“…Liu and Stevens [ 65 ] support the siting of wind energy infrastructure in mountainous regions and preferably above hilltops due to performance reasons. Several studies show that the development of renewable energy facilities in high-elevation mountainous regions often lacks of social acceptance [ 53 , 54 , 66 ]. This present study confirms prior findings.…”
Section: Discussionmentioning
confidence: 99%
“…This combination of energies could be especially applicable to small islands in the Mediterranean, as they have many commonalities such as size, available RESs, weather conditions, population, and environmental constraints [41]. On the other hand, the two most important parameters to consider while identifying the feasible locations are tourist activity and landscaping constraints [49] because tourism is one of the key economic activities [50] in most of the Mediterranean Sea islands, mainly in summertime. The Mediterranean region is one of the most popular tourist destinations in the world and attracts one-third of international tourists.…”
Section: Case Studiesmentioning
confidence: 99%
“…Devine-Wright [38] and Devine-Wright and Howes [39] identified the importance of the strength of place attachment and place identity among host communities in the acceptance of specific wind energy developments [38]. Other scholars [40][41][42][43] explored the role played by the "Not In My BackYard" (NIMBY) syndrome [44]. Smith and Klick [45], in particular, demonstrated that when people think about the advantages and disadvantages of wind farms, as they would if a wind farm were proposed for their community, their support for such technology diminishes.…”
Section: Introductionmentioning
confidence: 99%